10.1016/s1541-9800(09)70217-0 (CrossRef Listing of Deleted DOIs, 2000)
Opioid misuse and suicidal ideation (SI) are significant public health concerns in the United States, and incidence rates may be elevated among sexual minority people. We used data from the 2021 National Survey on Drug and Health (heterosexual, n = 39,647, lesbian/gay n = 1329, bisexual n = 3774) to investigate rates of opioid misuse and suicidal ideation (SI) across sexual identity groups. We found that opioid misuse (heterosexual, 3.0%, lesbian/gay, 5.2%; bisexual, 5.7%) and SI (heterosexual, 4.0%; lesbian/gay, 13%; bisexual, 23%) were highest among bisexual participants, followed by lesbian/gay participants, followed then by heterosexual participants. Further, opioid misuse and SI were associated across sexual identity groups (entire sample: r = 0.08, p < 0.001; heterosexual: r = 0.07, p < 0.001; lesbian/gay: r = 0.11, p < 0.001; bisexual: r = 0.082, p = 0.003). Notably, the association between opioid misuse and SI was strongest among sexual minority respondents. This work confirms a deleterious linkage between opioid misuse and SI and indicates that sexual minority participants were at greater risk for opioid misuse and SI as compared to heterosexual individuals. Clinicians should be cognizant of the risk of comorbid opioid misuse and SI in their sexual minority patients, as they develop and implement intervention strategies.